2013
DOI: 10.1155/2013/928290
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sex Steroid Hormones in Bacterial-Host Interactions

Abstract: Sex steroid hormones play important physiological roles in reproductive and nonreproductive tissues, including immune cells. These hormones exert their functions by binding to either specific intracellular receptors that act as ligand-dependent transcription factors or membrane receptors that stimulate several signal transduction pathways. The elevated susceptibility of males to bacterial infections can be related to the usually lower immune responses presented in males as compared to females. This dimorphic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
145
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 86 publications
4
145
0
1
Order By: Relevance
“…Although most of the relevant studies were performed on human or laboratory female animals, all data suggest that these sex steroid hormones play a key role in the modulation of interactions between bacterial microorganisms and the host's environment (Garcia-Gomez et al 2013). This bacterial-host communication can mediate the activation of virulence factors of microbial pathogens thus affecting the pathogenesis and prognosis of infection in their host organism (Hughes and Sperandio 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the relevant studies were performed on human or laboratory female animals, all data suggest that these sex steroid hormones play a key role in the modulation of interactions between bacterial microorganisms and the host's environment (Garcia-Gomez et al 2013). This bacterial-host communication can mediate the activation of virulence factors of microbial pathogens thus affecting the pathogenesis and prognosis of infection in their host organism (Hughes and Sperandio 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen and progesterone impact the composition of the gut microbiome through their effect on bacterial metabolism and growth and virulence of pathogenic bacteria (Mulak et al, 2014). An example of this is the susceptibility to Listeria monocytogenes infections in pregnancy partly due to elevated estrogen and progesterone levels, leading to adverse outcomes, including preterm delivery or stillbirth (Garcia-Gomez, Gonzalez-Pedrajo, & Camacho-Arroyo, 2013). Dramatic changes in ovarian hormones during the prenatal and postpartum periods also affect gut contractility and transit (Mayer, Savidge, et al, 2014).…”
Section: Hormonal Changes In Pregnancy and The Gut Microbiomementioning
confidence: 99%
“…Moreover, it has been suggested that sex hormones participate in signaling between pathogens and hosts; therefore, studies that reported sex-linked association of susceptibility to infectious disease may involve microbial responses (e.g. expression of virulence factors) other than just microbial proliferation [28]. Thus, it has been difficult to develop better criteria for identifying 'at risk' individuals, since it is a challenge to define the underlying mechanisms responsible for the reported associations between APO and periodontal disease, APO and certain oral community profiles, and/ or APO and specific oral pathogens.…”
Section: Introductionmentioning
confidence: 99%